An American Experience in Indonesia : The University of Kentucky Affiliation with the Agricultural University at Bogor - Beers, Howard W. (Howard Wayland), 1905- (Book collections on Project MUSE., 2015)
This book tells the story of an important experiment in international cooperation and inter-university collaboration in educational development. A team of educational and agricultural specialists from the University of Kentucky (called Kenteam in the book) lived and worked inBogor, Indonesia, from 1957 through 1965. Their purpose -- to work with the Agricultural University in Bogor to develop a complete college of agriculture to the level of capability for self-regeneration and growth. Working against a background of political and economic turmoil, Kenteam succeeded in helping the Indonesians b.